2019
DOI: 10.1007/s00122-019-03305-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic insights into morphometric inflorescence traits of wheat

Abstract: Key message Modifying morphometric inflorescence traits is important for increasing grain yield in wheat . Mapping revealed nine QTL, including new QTL and a new allele for the q locus, controlling wheat spike morphometric traits . Abstract To identify loci controlling spike morphometric traits, namely spike length (SL), internode length (IL), node number per spike (NPS), and node density (ND), we studied 146 Recombinant Inbred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 94 publications
4
28
1
Order By: Relevance
“…A different result was recorded when MTAs in this study were compared with known QTL for these five traits in previously published reports. The SL is one of the fundamental traits in spike architecture, and not only directly influences grain yield [55], but also significantly associated with HD [56]. This study confirms the significant relationship between SL and HD in durum wheat (P < 0.001), and four out of thirteen MTAs for SL here were associated with HD in durum wheat (Figs 2 and 3).…”
Section: Plos Onesupporting
confidence: 83%
“…A different result was recorded when MTAs in this study were compared with known QTL for these five traits in previously published reports. The SL is one of the fundamental traits in spike architecture, and not only directly influences grain yield [55], but also significantly associated with HD [56]. This study confirms the significant relationship between SL and HD in durum wheat (P < 0.001), and four out of thirteen MTAs for SL here were associated with HD in durum wheat (Figs 2 and 3).…”
Section: Plos Onesupporting
confidence: 83%
“…The present study also found that this region has a paracentric inversion when comparing the genetic order of our map to the physical position of this region in the CS Ref 1.0 assembly. Wolde et al (2019) mapped the TB-A1, which may have arisen from translocation of TEOSINTE BRANCHED1 (TB1) from the 4DS region to the 4AL region between 629.3 and 634.8 Mb, at almost the same position as we identified the 4AL FHB QTL. TB1 is known to play a role in controlling morphometric inflorescence traits in wheat, and we have previously identified QTL for spike density and flowering time that colocalize to the region (Zhang et al, 2018).…”
Section: Genetic Architecture Of Fhb Resistance Components and Their mentioning
confidence: 74%
“…Flowering time is largely thought of as controlling FHB infection through disease escape. However, it has recently become clear that the flowering period is also a key factor for wheat spikelet development, with many pleiotropic genes/QTL influencing the timing of flowering and development of spikes (Lewis et al, 2008;Shaw et al, 2013;Liu et al, 2019;Wolde et al, 2019;Chen et al, 2020). This shows that the influence of flowering time on FHB resistance is likely to be much more complex than previously expected.…”
Section: Genetic Architecture Of Fhb Resistance Components and Their mentioning
confidence: 99%
“…Three well‐known major genes affecting SD, that is Q , C and S1 , were located on chromosomes 5A, 2D and 3D, respectively (Prabhakararao, ; Kato, Sawada, & Miura, ; Liu, Liu, Dong, & Sun, ; Paillard et al, ; Sourdille et al, ; Xu et al, ). It is documented that flowering period (FP), controlled by three main groups of genes: vernalization ( Vrn ), photoperiod ( Ppd ) and earliness per‐se ( Eps ) (Distelfeld, Li, & Dubcovsky, ; Guedira et al, ; Nestor et al, ), is also a key factor for spikelet development in wheat (Guo, Chen, Roeder, Ganal, & Schnurbusch, ; Lewis, Faricelli, Appendino, Valarik, & Dubcovsky, ; Wolde, Trautewig, Mascher, & Schnurbusch, ; Zhang et al, ). Additionally, SD is also significantly related to plant height (PH) and spikelet number per spike (SNS) (Boden et al, ; Shaw, Turner, Herry, Griffiths, & Laurie, ; Worland et al, ).…”
Section: Introductionmentioning
confidence: 99%